(untitled) (Research, Society and Development, 2022)
Patients with chronic kidney disease often have impairment of nutritional status and this factor can interfere with the quality of treatment, favoring a worse prognosis. The purpose of this study was to verify the association of biochemical indicators, dialytic efficiency and nutritional status patients with chronic kidney disease on hemodialysis. This is a cross-sectional study performed with patients from a kidney disease center in Belém of Pará. The nutritional status was determined through the evaluation of the body mass index (BMI), biochemical data (albumin, phosphorus, potassium, hemoglobin, urea and glucose), Kt/V and urea reduction rate (URR). Data were tabulated and analyzed using the bioestat, version 5.0 and for static analysis of data was performed the Spearman correlation test considering a p<0.05. The sample consisted of 72 individuals, with a mean age of 19 to 79 years of which 50(69,4%) were male. Among the 72 patients, 33 (45,8%) presented eutrophy according to body mass index. Most of the population was adequate in relation to albumin, but the other parameters expressed altered measurement. Most patients had an adequate dialysis session due to the dialysis adequacy index. The correlation between nutritional status, phosphor and Kt/V was significant. It was concluded that most participants had adequate nutritional status and dialysis efficiency, with a significant correlation between them.